REPROCESS AND REPAIR COW UPPER LEATHER SUEDE WITH SPRAY FINISH METHOD - Sofwan Siddiq Abdullah (Politek ATK Yogyakarta Press, 2022)
Upper leathers have many types of leather articles likes nappa leather upper, sports shoe upper, suede upper leather and others. Suede upper leather is upper leather that has own charm because have more fashionable nap. Making suede leather more difficult because the raw materials used in this process is the upper suede leather raw material that does not pass because the color does not meet customer desires (leather from industrial leather stock). The basic color of suede skin is absolute produced through Post Tanning process. Beside the color, a feeling touch is also expected in upper suede leather. Suede skin repair process done in two ways: wet process (Post Tanning) and spray finish method. Spray finish method can save cost and time in repairing suede leather. The process of color and quality improvement is done with the finishing process so as to get suede leather in accordance with the wishes. The chemicals used in this process are: Water, metal complex dyestuff, 1441 UR, Amollan IP and Rosilk TM 2000. Suede skin repair process using spray finish method. The upper suede leathers are tested by organoleptic test. The results of this study obtained leather upper suede leathers have met the standards.